The Effect of Using the Crossword Puzzle Strategy on Developing Kindergarten Children's Writing Skills - Abeer Ayman Abdul Latif Al-Khudour; Mustafa Misbah Miloud Sahboun (Journal of Libyan Academy Bani Walid, 2025)
This research aims to identify the writing skills required for kindergarten children, identify the foundations for using the crossword puzzle strategy in developing the writing skills of kindergarten children, and identify the proposed concept for using the crossword puzzle strategy in developing writing skills. It also aims to identify the effectiveness of this strategy in developing writing skills. To conduct this research, the researcher reviewed previous literature and previous studies to compile a theoretical framework, identify study variables, the research methodology, and the study tools used. The researcher also wrote the theoretical aspect of the crossword puzzle strategy and writing skills, recalculated the reliability of the study tools, applied the study tools to the sample, collected and analyzed data, arrived at and interpreted the study results, and presented recommendations and proposals. The research tool used was a writing skill test. The test consisted of (4) questions and two games. The study found that there are differences between the average scores of children before applying the crossword puzzle strategy and their average scores after applying the strategy. This confirms the effectiveness of this strategy in developing writing skills among kindergarten children. There are also differences between the average scores of the children of the experimental group on the post-test of the crossword puzzle strategy. This confirms the effectiveness of this strategy in developing writing skills among kindergarten children in favor of the experimental group and the children’s superiority over their peers in the control group in the writing skills test. Through this research, the researcher suggested studying the effect of the crossword puzzle strategy for a longer time and at other educational levels and conducting comparative studies between teaching methods and strategies to show which are the most feasible and effective.